An Evaluation Of The Cambridge English For Job Hunting Textbook Through The Lens Of Tomlinson's Theory: A Comprehensive Analysis Of Content And Effectiveness - Abdul Syahid; Josilia Puspito Rahayu; Muhamad Ario Setiawan; Rizki Novia Darma; Syarif Hidayat (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This study is aimed to investigate the compatibility of materials in the textbook entitled "Cambridge English for Job-hunting" based on Tomlinson’s theory. The researcher used descriptive approach research as the type of the study. The data of the study were done by follows the process involved several stages, which are as follows: 1) The researcher selected an English textbook for analysis, 2) the researcher read the English textbook thoroughly, 3) the researcher carefully reviewed the content of the textbook, 4) the researcher gathered all the necessary materials from the textbook for analysis. The result of this study shows that the textbook substantially complies with Tomlinson's criteria for useful tools for language learning. It effectively engages students, builds confidence, offers appropriate information, uses actual speech, and accommodates a range of learning preferences and emotional conditions.